Exploiting Fog Computing in Health Monitoring - Gia, Tuan Nguyen; Jiang, Mingzhe (Fog and Edge Computing, 2019)
This chapter exploits fog computing in health‐monitoring Internet‐of‐Things (IoT) systems for enhancing the quality of healthcare service. It shows an overview of the architecture of an IoT‐based system with fog computing. Fog computing services locating in a fog layer of smart gateways are diversified for serving IoT applications. The chapter discusses the fog computing services in smart e‐health gateways. The health‐monitoring IoT system consists of several wearable sensor nodes, smart gateways with fog services, cloud servers, and terminals. The chapter discusses detailed implementations of these components. It provides a case study, experimental results, and evaluation related to heart rate variability (HRV) analysis. The chapter presents the related applications in fog computing and discusses future research directions. Fog computing demonstrates that it is one of the most suitable candidates for augmenting IoT systems in healthcare and other domains.